Trade Game Akuntasi Untuk Siswa Sekolah Menengah Atas - Dwi Iga Luhsasi; Carolina Lita Permatasari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
Almost all students who have difficulty in understanding accounting material. Only a few students can understand thoroughly. Most of the students are oriented only to the result of the exercise from the questions, not the understanding of the process, especially for trading company accounting cycle topic. This material requires more understanding in every process of preparation until the preparation of financial statements. The focus on calculating inventory and cost of goods sold makes students often reluctant to do and understand it. This condition also felt by Sedes Sapientiae High School Semarang students. The more complicated cycle requires more attention, sometimes make the students less patient in understanding the cycle. Based on this condition, a tool is needed to solve the problem, which is the Accounting Trade Game. The aim of this game is to attract more attention to students in the learning process on accounting economics subject especially for trading company accounting cycle. In order to solve this problem, development research was carried out using the Borg and Gall model. This model consists of a preliminary study stage, preparation of a product draft, also development and evaluation of the product. As the result, a tool called Accounting Trade Game is a good tool which means that it can help students in the learning the material.